Comparison of microwave and conventional heating methods in carbonization of polyacrylonitrile-based stabilized fibers at different temperature measured by an in-situ process temperature control ring. (June 2017) - Jin, Shuangling; Guo, Chenting; Lu, Yonggen; Zhang, Rui; Wang, Zhanyong; Jin, Minglin
Abstract: The pre-oxidized fibers were carbonized by microwave heating and conventional heating, respectively. The temperature in the two processes was calibrated by a process temperature control ring that was wrapped by the fibers. The microwave carbonized fibers (MCFs) fabricated at 750–1000 °C possess the higher carbon content, larger average crystallite dimensions (La and Lc ), higher porosity, and more homogeneous structure along cross-section than those of conventionally carbonized fibers (CCFs) obtained at the same temperature. However, when the temperature reaches 1000 °C and above, the crystallite sizes of MCFs are smaller than those of CCFs fabricated at the same temperature, and the difference between the skin and core structure becomes larger as the temperature increases for MCFs. The tensile strength and modulus of MCFs are higher than those of CCFs obtained at 750–1000 °C, while the mechanical properties for MCFs and CCFs obtained at temperature above 1000 °C is close. This phenomenon could be attributed to the temperature dependence of microwave adsorption ability of the as-obtained CFs.